Machiavelli: Ambition, Freedom and Justice - Ezcurra, Alicia Villar (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This article tackles the anthropological conception of Machiavelli, mainly taken from the Discourses on the First Decade of Titus Livius in which stands out the identity of human passions and the importance of its understanding to reach political knowledge. Machiavelli considers that the human being is malleable in such a way that a passion can be fought and compensated by another one. From this perspective, is analysed the role of ambition and freedom both as a source of confrontation and degeneration and as an incentive to achieve the most important goals.